1990
DOI: 10.1146/annurev.ms.20.080190.002135
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Thin Films

Abstract: where the term 3/L is the boundary area per unit volume and the term dR=dL/2 represents an incremental movement of the boundary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 2 publications
1
32
0
Order By: Relevance
“…We expect that a similar model would provide a good description of the flow stress as a function of temperature. The diffusion-facilitated grain boundary sliding mechanism is also consistent with the observation that the 960 nm film is much stronger than the 450 nm film (Table II), in contrast to the usual notion that smaller is stronger where thin films are concerned [9][10][11]. Within the context of the Ashby model, this anomaly is readily explained as a grain size effect.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We expect that a similar model would provide a good description of the flow stress as a function of temperature. The diffusion-facilitated grain boundary sliding mechanism is also consistent with the observation that the 960 nm film is much stronger than the 450 nm film (Table II), in contrast to the usual notion that smaller is stronger where thin films are concerned [9][10][11]. Within the context of the Ashby model, this anomaly is readily explained as a grain size effect.…”
Section: Discussionsupporting
confidence: 83%
“…As a result, metal thin films, which are key components in these devices, have been studied extensively. These investigations have demonstrated that the mechanical properties of thin films are generally very different from those of their bulk counterparts [1][2][3][4][5][6][7][8][9][10][11] and that they depend on whether the film is freestanding or supported by a substrate [12][13][14][15]. Understanding the mechanical behavior of metal thin films at elevated temperature is essential for the design of reliable devices, which often operate above room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…66,70,71 The mechanical properties of UTCs differ from their bulk counterparts due to differences in processing, size, material composition, and microstructure. [72][73][74] A comparison of Young's modulus E and the Poisson's ratio 68 of several materials frequently used in flexible electronics [e.g., singlecrystal Si, hydrogenated amorphous (a-Si:H), hydrogenated nanocrystalline Si (nc-Si:H), polycrystalline Si, Kapton V R , and polyethylene naphthalate (PEN)] is given in Table I. [75][76][77][78][79][80][81][82] The experimental techniques that have been used to study mechanical aspects of UTCs include (i) direct methods 83,84 such as xray diffraction 85,86 and micro-Raman spectroscopy 87,88 and (ii) indirect methods based on measuring the curvature 89 (e.g., optical interferometry, 90 laser scanning, 91,92 and microscope image monitoring in real time 43 ).…”
Section: Ultra-thin Chips and Mechanical Bendingmentioning
confidence: 99%
“…Several studies and reviews of the mechanical behavior of thin films have appeared in the literature (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). These show the variety of test techniques that have been developed, and results that have been obtained.…”
Section: Mechanical Testing Of Thin Filmsmentioning
confidence: 99%